Perbedaan Sikap Kemandirian Anak Usia Dini pada Masa Pandemi ditinjau dari Ibu Bekerja dan Ibu Tidak Bekerja di TK Kartika X-5 Pusdik Arhanud - Elis Indah Setyowati; Tomas Iriyanto; Nur Anisa; Elis Indah Setyowati; Tomas Iriyanto (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2022)
Abstract: The attitude of independence of early childhood during the pandemic is influenced by two factors, namely the mother's employment status and the mother's level of education. This is due to the lack of support and motivation for children to learn because of the mother's limited time in accompanying children's learning at home. The purpose of this research is to find out the difference in the attitude of independence of children who are cared for by working and non-working mothers during the pandemic at Kartika X-5 Kindergarten of Pusdik Arhanud. Researchers used comparative quantitative research methods. This study has 2 variables, namely the attitude of independence of early childhood and the work status of the mother. The research sample was taken using a proposive sampling technique, meaning that all samples came from a population of 56 respondents consisting of 12 working mothers and 44 non-working mothers at Kartika X-5 Pusdik Arhanud Kindergarten. The data collection technique used a Likert scale which was then analyzed using an independent sample t-test through SPSS 25. The results showed the acquisition of a significance value (α) of 0.05 and obtained p equal to 0.000 and obtained a t-table of 8.068 and P value (0.00 less than 0.05). So Ho is rejected and Ha is accepted, with a mean value of independence of children aged 4-5 years who are cared for by working mothers as much as 71,500 and mothers not working as much as 86.43. This shows that there are differences in the attitude of independence of early childhood during the pandemic in terms of working mothers and mothers not working at Kartika X-5 Kindergarten of Pusdik Arhanud. Abstrak: Sikap kemandirian anak usia dini pada masa pandemi dipengaruhi oleh dua faktor yakni status pekerjaan dan tingkat pendidikan ibu. Hal ini disebabkan anak kurang memperoleh dukungan dan motivasi belajar sebab keterbatasan waktu ibu dalam mendampingi belajar anak di rumah. Tujuan pelaksanaan penelitian guna mengetahui perbedaan sikap kemandirian anak yang diasuh oleh ibu bekerja dan tidak bekerja pada masa pandemi di TK Kartika X-5 Pusdik Arhanud. Peneliti menggunakan metode penelitian kuantitatif komparatif. Penelitian ini memiliki 2 variabel yaitu sikap kemandirian anak usia dini dan status pekerjaan ibu. Sampel penelitian diambil menggunakan teknik proposive sampling, artinya seluruh sampel berasal dari populasi dengan jumlah 56 responden yang terdiri dari 12 ibu bekerja dan 44 ibu tidak bekerja di TK Kartika X-5 Pusdik Arhanud. Teknik pengumpulan data mengunakan skala likert yang kemudian di analisis menggunakan uji independent sampel t-test melalui SPSS 25. Hasil penelitian menunjukkan nilai Sig. 2-tailed sebesar 0,000 dan t-tabel sebesar 8,068 sehingga P value (0,00 kurang dari 0,05), maka dapat dinyatakan Ho ditolak dan Ha diterima. Kemudian didukung dengan perolehan nilai mean kemandirian anak usia 4-5 tahun dari ibu bekerja sebanyak 71,500 dan ibu tidak bekerja sebanyak 86,43. Hal ini menunjukkan adanya perbedaan sikap kemandirian anak usia dini pada masa pandemi ditinjau dari ibu bekerja dan ibu tidak bekerja di TK Kartika X-5 Pusdik Arhanud.